Panax notoginseng saponins attenuated cisplatin-induced nephrotoxicity - Liu Shi-Jie; Zhou Shi-Wen (Acta Pharmacologica Sinica, 2016)
"AIM: To study protective effects of Panax notoginseng saponins (PnS) against cisplatin-nephrotoxicity. METHODS: Cisplatin-induced nephrotoxicity in mice in vivo, and primary culture of rabbit proximal tubular cells (PTC) in vitro were established. Blood urea nitrogen, serum creatinine, cell viability, DNA interstrand cross-link, DNA-protein cross-link, and cytosolic free [Ca2+]i were assayed with diacetyl monoxime, alkaline picrate, trypan blue, ethidium bromide binding, 125I-postlabelling, and Fur 2-AM, respectively. RESULTS: With pretreatment for 2 d in mice, PnS 100 and 200 mg.kg-1.d-1 suppressed cisplatin-induced high blood urea nitrogen level to 83% and 31%, and serum creatinine level to 86% and 42%, respectively (P < 0.01). Preincubated with PTC for 24 h, PnS 10 and 100 mg.L-1 inhibited cisplatin-induced decrease of cell viability from 78% to 81% (P < 0.05) and 89% (P < 0.01), respectively. PnS 10 and 100 mg.L-1 suppressed formations of DNA interstrand cross-link to 47% and 40%, DNA-protein interstrand cross-link to 77% and 42%, and cytosolic free [Ca2+]i overload in PTC to 70% and 63%, respectively. (P < 0.01). CONCLUSION: PnS was a prophylactic for cisplatin-induced nephrotoxicity, and mechanisms were relevant to the effects that PnS reduced cisplatin-induced cytosolic free [Ca2+]i overload, and formations of DNA interstrand cross-link and DNA-protein cross-link."